1995
DOI: 10.2307/1131947
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Interaction Quality as a Partial Mediator of the Roles of Maternal Depressive Symptomatology and Socioeconomic Status in the Development of Child Behavior Problems

Abstract: This investigation examined the relation between maternal depressive symptomatology and the development of externalizing behavior problems in children by incorporating mother-child interaction quality into a series of models. A representative sample of 376 first-grade boys and girls (mean age = 6.52) from diverse backgrounds (234 from the lowest 2 socioeconomic classes) and their mothers completed an interaction task designed to measure the quality of mother-child interaction. Latent variable structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 31 publications
5
97
0
2
Order By: Relevance
“…Chronic and/or acute stressors outside the family can also moderate the impact of parental mental illness on children. More specifically, the stress associated with minority status, low levels of education, single parenthood, social isolation and poverty increases the likelihood of emotional and behavioral problems in children of parents with mental illness (Beidel & Turner, 1997;Hammen et al, 1987;Harnish et al, 1995;Sameroff & Seifer, 1983). Moreover, in families with a parent with depression where stress was low, support high, and depressive symptoms less severe, significantly fewer children exhibited mental health problems than children from all families with a parent with depression (10% v. 25%; Billings & Moos, 1983).…”
Section: Moderators Of the Relationship Between Parent Mental Illnessmentioning
confidence: 99%
“…Chronic and/or acute stressors outside the family can also moderate the impact of parental mental illness on children. More specifically, the stress associated with minority status, low levels of education, single parenthood, social isolation and poverty increases the likelihood of emotional and behavioral problems in children of parents with mental illness (Beidel & Turner, 1997;Hammen et al, 1987;Harnish et al, 1995;Sameroff & Seifer, 1983). Moreover, in families with a parent with depression where stress was low, support high, and depressive symptoms less severe, significantly fewer children exhibited mental health problems than children from all families with a parent with depression (10% v. 25%; Billings & Moos, 1983).…”
Section: Moderators Of the Relationship Between Parent Mental Illnessmentioning
confidence: 99%
“…Because depressive disorders are developmental in nature (Fergusson, Horwood, Ridder, & Beautrais, 2005) and because women who have experienced IPV are more likely to develop mental disorders when exposed to subsequent trauma (Breslau, Chilcoat, Kessler, Peterson, & Lucia, 1999), understanding how IPV contributes to depressive symptoms among adolescent mothers can lead to better specified prevention and treatment interventions. In addition, maternal depression moderates a number of important child outcomes, including children's externalizing behavior (Harnish, Dodge, & Valente, 1995), children's internalizing behavior (Cicchetti, Rogosch, & Toth, 1998) and their adaptive functioning (Luoma et al, 2001), so preventing depression among adolescent mothers has clear benefits for them and their children.…”
Section: Introductionmentioning
confidence: 99%
“…Harnish et al (1995) found that maternal harshness mediated the association between maternal depressive symptoms and child adjustment in the first grade in a high-risk sample. Dannemiller (1999) observed that the effects of maternal depression on cognitive and language outcomes were partially accounted for by levels of maternal sensitivity.…”
Section: Attachment Disorganization and Early Maternal Carementioning
confidence: 86%